Precious‐Metal‐Free Electrocatalysts for Activation of Hydrogen Evolution with Nonmetallic Electron Donor: Chemical Composition Controllable Phosphorous Doped Vanadium Carbide MXene. (4th June 2019) - Yoon, Yeoheung; Tiwari, Anand P.; Choi, Min; Novak, Travis G.; Song, Wooseok; Chang, Hyunju; Zyung, Taehyoung; Lee, Sun Sook; Jeon, Seokwoo; An, Ki‐Seok
Abstract: The insufficient strategies to improve electronic transport, the poor intrinsic chemical activities, and limited active site densities are all factors inhibiting MXenes from their electrocatalytic applications in terms of hydrogen production. Herein, these limitations are overcome by tunable interfacial chemical doping with a nonmetallic electron donor, i.e., phosphorization through simple heat‐treatment with triphenyl phosphine (TPP) as a phosphorous source in 2D vanadium carbide MXene. Through this process, substitution, and/or doping of phosphorous occurs at the basal plane with controllable chemical compositions (3.83–4.84 at%). Density functional theory (DFT) calculations demonstrate that the PC bonding shows the lowest surface formation energy (Δ G Surf ) of 0.027 eV Å −2 and Gibbs free energy (Δ G H ) of –0.02 eV, whereas others such as P‐oxide and PV (phosphide) show highly positive Δ G H . The P3–V2 CTx treated at 500 °C shows the highest concentration of PC bonds, and exhibits the lowest onset overpotential of –28 mV, Tafel slope of 74 mV dec −1, and the smallest overpotential of ‐163 mV at 10 mA cm −2 in 0.5m H2 SO4 . The first strategy for electrocatalytically accelerating hydrogen evolution activity of V2 CTx MXene by simple interfacial doping will open the possibility of manipulating the catalytic performance of various MXenes. Abstract : The phosphorization reactions with adjustable components ensure effective and tunable P‐doping (3.83–4.84 at%) with controllable chemical composition into V2 CTx MXene, via varying reaction temperatures (300–500 °C). Most importantly, P3‐V2 CTx which has mainly PC bonds, exhibits the smallest overpotential of −163 mV (onset, 28 mV) and a lower Tafel slope of 74 mV dec −1 for the hydrogen evolution reaction.